Phase Studies of Complex Polyelectrolyte Mixtures - Axenstrand,Magdalena (2019)
Complex coacervation is a type of liquid-liquid phase separation, that occurs when oppositely charged macroions are mixed in aqueous solution under certain conditions. It has been proven to have applications within many different industries including the food and pharmaceutical industries. For example, protein/polysaccharide coacervates have been used for their emulsifying and foaming properties. Additionally, complex coacervate can be utilized for encapsulation of sensitive compounds such as flavors. In pharmaceutics, this phenomenon has also successfully been used to encapsulate therapeutic agents such as proteins and lipophilic substances, in an attempt to improve their efficiency and delivery. Other application areas include production of carbonless copy paper and fragrance samples. Despite the interest in complex coacervation within many different fields, the phenomenon and its underlying driving forces are still poorly understood. The most common theory is that the process is initially driven by electrostatic attractions between opposite charges on the macroions, followed by an entropic gain from release of counterions and rearrangement of water molecules. The purpose of this study was to better understand the concept of complex coacervation and how it is affected by different parameters. A model system comprising polyacrylic acid (pAA) and ε-poly-L-lysine was used to investigate the impact of salt concentration, pH and degree of polymerization on coacervate formation and composition. Water content was analyzed by freeze drying, a nitrogen and protein analyzer was used to measure the EPL content and salt ion levels were measured with potentiometry. Since pAA could not be analyzed, a mass balance was required to determine the composition of the two phases created upon phase separation. It was found that all three parameters influenced phase composition. Increasing the salt concentration led to higher water content; presumably due to a loosening of the polymer network. It also resulted in lower concentration of both polymers in the coacervate. However, interestingly, the molar ratio between the polymers remained relatively constant over all salt concentrations. A similar decrease in polymer concentration was observed as the limits of the pH window for coacervation were approached. Furthermore, higher degree of polymerization generated more viscous coacervates with lower water content and resulted in a higher critical salt concentration. Unfortunately, the reason for many of the observations were difficult to explain, which is why further research is necessary. It would be of particular interest to investigate how these parameters influence the structure of the coacervate. Additionally, more research on the thermodynamics of complex coacervation is crucial for increasing the understanding of this complex phenomenon.
Keywords: coacervate; coacervation; phase separation; polyelectrolytes; pharmaceutical technology; läkemedelsteknologi